General dry trends according to the standardized precipitation evapotranspiration index in mainland Chile - Meseguer-Ruiz, Oliver; Serrano-Notivoli, Roberto; Núñez-Hidalgo, Ignacio; Sarricolea, Pablo (Frontiers in Earth Science, 2024)
Droughts are one of the main challenges affecting humanity in a global change context. Due to its spatial configuration, Chile experiences droughts of different severities, from arid to humid climates, ranging from sea level to elevations above 6,000 m above sea level (a.s.l.), but it is still unknown how this phenomenon behaves in distribution, duration and intensity. The goal of this study is to identify how droughts have affected the different climate regions of the country between 1979 and 2019. The Standardized Precipitation Evapotranspiration Index (SPEI), calculated for March and September, at the end of the humid season in the north and center-south of the country, respectively, and calculated at 3-, 6-, 9-, 12- and 24-month, allowed to determine the trends of the drought severity in a 5 × 5 km grid between 1979 and 2019. We found that negative and significant trends, indicating dry conditions, appear mainly in the Andes above 2,000 m a.s.l., where the main water reservoirs are located, affecting all climate types, except Mediterranean ones between 33°S and 38°S. The SPEI indicates general trends towards drier conditions across various elevations and climate types, with more pronounced negative trends in the north and central regions and some positive trends in the south. These trends suggest a significant impact on water availability, and highlight the need for focused policy initiatives to combat drought effects and manage water resources effectively. These findings are of main interest to Chile, one of the world’s leading producers of lithium and copper, with both industries requiring substantial amounts of water for extraction and processing, demanding high water availability in a drier territory.